2023
DOI: 10.1039/d3ra00024a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic spray pyrolysis synthesis of TiO2/Al2O3 microspheres with enhanced removal efficiency towards toxic industrial dyes

Abstract: Developing low-cost and highly effective adsorbent materials to decolorate wastewater is still challenging in the industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…8,9 To address these issues, numerous approaches have been attempted to develop highly active photocatalysts that can absorb more visible light and have low carrier recombination rates. 10,11 In recent years, researchers have identied and demonstrated that numerous defective metal-oxide semiconductors containing oxygen vacancies, such as TiO 2 , 12,13 ZnO, 14 CeO 2 , 15 and WO 3 (ref. 16) exhibit superior catalytic reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 To address these issues, numerous approaches have been attempted to develop highly active photocatalysts that can absorb more visible light and have low carrier recombination rates. 10,11 In recent years, researchers have identied and demonstrated that numerous defective metal-oxide semiconductors containing oxygen vacancies, such as TiO 2 , 12,13 ZnO, 14 CeO 2 , 15 and WO 3 (ref. 16) exhibit superior catalytic reactivity.…”
Section: Introductionmentioning
confidence: 99%